Efisiensi Teknis Pada Aglomerasi Ekonomi Di Industri Manufaktur Di Provinsi Jawa Timur - Pramudiyani, Dewita Ike; Restikasari, Wenny (Jurnal Ekonomika : INDEPENDEN, 2023)
The industrial sector has become a leading sector and contributes greatly to the formation of GRDP in East Java. However, the contribution is still not optimal due to other factors that hinder the production process in each industry. One form of externality that can encourage regional growth is the agglomeration economy. This study aims to determine the role of economic agglomeration on tchnical efficiency in the manufacturing industry in East Java. The stochastic frontier analysis method is used to determine the technicala efficiency in East Java. The result showed that the technical efficiency of manufacturing industry companies in East Java in 2010-2014 was not efficient. The value of technical efficiency of the industry from 2010-2014 the results show fluctuations. These findings show that the TE value is not efficient, so the recommendation given is the need to increase the size of the company to encourage higher efficiency.